Perilaku Ibu Ketika Hamil dalam Upaya Pencegahan Anak Lahir Stunting di Kabupaten Kampar - Dewi Anggriani Harahap; Zakkiyatus Zainiyah; Yan Sartika (Jurnal Kesehatan Komunitas, 2023)
The prevalence of child stunting in Indonesia is still high. In 2021 at the national level stunting was at 24.4%. Stunting is caused by nutritional problems that are chronic or long-lasting. The theory of planned behavior is used as a basis for knowing the behavior of preventing stunting in children during pregnancy in mothers, while the concept of family-centered nursing is used as a basis for identifying the role of family support and environmental support in its influence on maternal behavior in preventing stunting in children. This study aims to determine the behavior of preventing stunting children when pregnant women at Puskesmas Lipat Kain, Kampar Regency. Analytical research type with cross-sectional design. The sample was 72 pregnant women at Puskesmas Lipat Kain. Independent variables consist of knowledge, attitudes, cultural values, family support, and environmental support, while the dependent variable is stunting prevention behavior. Questionnaire research instruments that have been tested for validity and reliability, are collected by observation. Univariate and bivariate data analysis. The p-value that is most associated with stunting prevention behavior in children when pregnant women are family support and environmental support is 0.000 (<0.05). In addition, knowledge (0.009), attitudes (0.018), and cultural values (0.017) also showed a relationship with the behavior of preventing child stunting during pregnancy.